2013
DOI: 10.1016/j.jor.2013.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Computational modelling of long bone fractures fixed with locking plates – How can the risk of implant failure be reduced?

Abstract: For the clinical use of the LCP as a locked internal fixator in fractures with an interfragmentary gap of 1 mm, at least two to four plate holes near the fracture gap should be omitted to allow fracture motion and bone contact to occur. This will also achieve a larger area of stress distribution on the plate and reduce the likelihood of fatigue failure due to cyclic loading.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
1
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 16 publications
2
32
1
1
Order By: Relevance
“…18 Results are also consistent with a previous study which showed minimal effect of the fracture gap on construct stiffness in axial loading. 21 Increased working length resulted in decreasing the stiffness of fracture fixation and increasing interfragmentary movement, and this is consistent with previous studies. 9,18,19,29 The effect of working length on plate stress in axial loading is in agreement with the study of Stoffel et al .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…18 Results are also consistent with a previous study which showed minimal effect of the fracture gap on construct stiffness in axial loading. 21 Increased working length resulted in decreasing the stiffness of fracture fixation and increasing interfragmentary movement, and this is consistent with previous studies. 9,18,19,29 The effect of working length on plate stress in axial loading is in agreement with the study of Stoffel et al .…”
Section: Discussionsupporting
confidence: 92%
“…Working length between screws was previously reported as an important parameter for affecting axial and torsional stiffness 19,21,29 and interfragmentary movement at the fracture gap. 18 Results are also consistent with a previous study which showed minimal effect of the fracture gap on construct stiffness in axial loading.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A fracture gap of 1 mm was assumed [22]. The interfaces between the HA-BG plate and humerus bone were treated as unpenetrated interfaces, while the contact interaction between the plate and the bone was defined as having coefficient of friction 0.3 [23].…”
Section: Finite Element Analysismentioning
confidence: 99%
“…Um dos mais importantes é o cálculo do comprimento da área de trabalho durante a fixação da fratura, definida pela distância entre os parafusos mais próximos ao foco da fratura proximal e distalmente. 10 Acredita-se que a tensão é mais baixa na placa quando a área de trabalho é pequena. 9 Idealmente, em uma fratura de traço simples transverso, espera-se que a mobilidade interfragmentar seja igualmente dividida entre o implante e o lado oposto do osso, quando uma carga é exercida de forma axial.…”
Section: Introductionunclassified